Cytotoxic Activity of Juniperus excelsa M. Bieb. Leaves Essential Oil in Breast Cancer Cell Lines - Mahnaz Khanavi; Aysheh Enayati; Mohammad Reza Shams Ardekani; Tahmineh Akbarzadeh; Elahe Karimpour Razkenari; Mahdieh Eftekhari* (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Juniperus excelsa is a flowering plant that has been applied as traditional medicine for treatment of various disorders such as dysmenorrhea, bronchitis and colds, jaundice and tuberculosis. The aims of the present study were analyzing J. excelsa essential oil and investigation of its cytotoxic activity on three breast cancer cell lines.  Methods:  Juniperus excelsa leaves were collected from Dena mountains, located in the south-west of Iran. The composition of the essential oil was analyzed by gas chromatography-mass spectrometry (GC/MS). Cytotoxic activity was evaluated using MTT assay.   Results: Forty-one components, related to 99.83% of the total oil, were identified. Monoterpene hydrocarbons represented the major components of the volatile oil while α-pinene (73.27%) was the major component. The essential oil showed significant cytotoxic activity against breast cancer cell lines MCF-7 (IC50=0.084 µg/mL), MDA-MB-231 (IC50=0.090 µg/mL) and T-47D (IC50=0.124 µg/mL).  Conclusion: The analysis of J. excelsa oil revealed α-pinene and cedrol as the main compounds of the volatile oil that could justifiy its remarkable cytotoxic effect against the tested cell lines.